Foucault, Fairclough and Post-Development Discourse Analysis - Dana Ibrahim Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Post-Development-inspired thinking is rooted in a critical view of modernity from a Post-Modern perspective. This field is strongly influenced by the thoughts and works of Michel Foucault. Studies in this direction have been done to analyze the concept of development to reveal the role and function of power and knowledge in the discourse of development. This article explores the topic of Post-Development, which reveals the concept of Post-Development through a review of Foucault’s thought and intellectual framework and some of the initial and incorrect interpretations left out in this regard. All these analyses are carried out under the three-layered theoretical framework of Fairclough and especially the third layer of this model, which considers explanation as to the ultimate goal of the study of discourse in relation to society in the field of critical speech analysis. Scattered and weak discussions around this axis are due to the misuse of Foucault’s thoughts. Therefore, in this article, we seek to expose the post-Development discourse as much as possible by using Foucault’s ideas about knowledge and power, which are the source of development.